Cultural Rights and Policies in the Department of Santander, Colombia, 2008-2011 - Otero Torres, Eduardo; Rodríguez Hernandez, Hernán; Rodríguez Duarte, María Alejandra (DIXI, 2016)
Introduction: In recent years, we have witnessed a process of institutionalization and formalization of culture in the country through the adoption of cultural rights, consolidation of cultural legislation, and creation of the Ministry and secretaries of culture, among other factors. At the same time, we have witnessed major transformations at the level of discourse, such as the notions of cultural development and cultural pluralism that are centrally promoted by unesco. Methodology: To describe the national and international context of policies on culture and examine the general framework of cultural policies in the department of Santander (Colombia), detailing the various programs that form the core cultural strategies and analyzing indicators of each strategy. Result: We have demonstrated changes in the filds of communications and the economy, where culture has begun to take on a central role in gdp, though it is yet to have signifiant importance in the policies of our governments. Conclusions: Th diffilty of grasping the cultural dimension—which vacillates between the artistic and anthropological spheres—generates imprecision in programs and diffilty in the conception of the link between culture, development, and democracy.